(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Community food security (CFS) attempts to bring out the nuances in food security analysis, especially the age-long misconception of equating food availability with food security. Under this new paradigm, food security is achieved only when communities obtain a safe, culturally and socially acceptable, nutritionally adequate diet through a sustainable food system that maximizes community self-reliance and social justice. A four-stage sampling approach was adopted to select respondents in the six communities adjacent to Federal University Dutse, Jigawa State. Data were collected using a questionnaire from 184 households in the communities and analysed using descriptive statistics and the Household Hunger Scale (HHS) and the Household Food Insecurity Access Scale (HFIAS) to determine the food security status of the communities and the Problem Confrontation Index to determine the constraints to CFS. Results showed weak infrastructural support without educational, health, financial, and agricultural support systems. Further, results showed that 59.24 and 24.46% of the respondents experienced moderate and severe hunger, respectively, while 16.30% were without hunger. The prime constraints to sustainable community food security hovered around insufficient farmland (PCI = 273), drought (PCI = 267), lack of agricultural facilities (PCI = 266), and high cost of farming inputs (PCI = 256). Conclusively, the study revealed that food insecurity (hunger) is endemic (83.70%) in the adjunct communities, and concerted efforts should be targeted at improving the infrastructural base of the communities